VAGUS ACTIVATION AS A MEANS OF CORRECTION OF NEUROGENIC-BORNE ARRHYTHMIAS - Strakolist, H. M.; Bogdanovska, N. V.; Bessarabova, O. V. (Rehabilitation and Recreation, 2024)
The article considers the possibility of using technique of diaphragmatic breathing “vacuum” for the prophylaxis and correction of neurogenic-borne arrhythmias. It is noted that under the influence of chronic stress, the tone of the sympathetic nervous system inevitably increases, what negatively affects the regulation of the cardiovascular system and leads to rhythm disturbances. By controlling breathing, it is possible to indirectly influence the tone of the sympathetic and parasympathetic divisions of the autonomic nervous system. The direct effect on heart rate is caused by a change in the vagal tone. In the walls of the esophagus, stomach and bowels there are numerous fibers of the vagal nerve, which are actively stimulated during the “vacuum” exercise. This causes a strong and rapid parasympathetic effect. The purpose of the research is correction of neurogenic-borne arrhythmias using technique of diaphragmatic “vacuum” breathing and providing recommendations for preventing the progress of these arrhythmias. Research material and methods: analysis of methodological literature and information sources by the research topic; instrumental research methods; analysis of temporal and spectral indicators of heart rate variability of investigated people (n=19); methods of mathematical statistics. The results. The importance of breathing in the mediated effect on the shift in the ratio of sympatho-parasympathetic influences on the regulation of the cardiovascular system and heart rhythm is shown. The dynamics of the following investigated indicators were analyzed: heart rate, frequency domain indicators (Hz) – VLF, LF, HF, TR, which reflect the activity of neurohumoral influences on the heart rhythm; values of the maximum amplitude of spectral peaks (ms2/Hz) – VLF, LF, HF and the index of vagosympathetic interaction LF/HF; RRNN – average duration of RR intervals; SDNN is the standard deviation of the values of normal RR intervals. Conclusions. The analysis of the obtained experimental data allows to recommend the use technique of “vacuum” diaphragmatic breathing for the prevention and correction of neurogenic-borne arrhythmias. As part of neuromodulation vagus activation can be used in the treatment of such diseases as depression, obesity, diseases of the gastrointestinal tract, lung diseases, which can complicate the course of cardiac pathology, as well as stress. We consider that vagus activation can be used in complex treatment, in combination with traditional drug therapy approaches.